2020
DOI: 10.1007/s10745-020-00132-w
|View full text |Cite
|
Sign up to set email alerts
|

Natural Plant Resources for Sustainable Development: Insights from Community Use in the Chimanimani Trans-Frontier Conservation Area, Mozambique

Abstract: In rural African communities, wild plant species are a valuable resource that are often threatened by agricultural conversion and overexploitation. To understand the harvest and sale of wild plant species that provide fruits and raw materials for artisanal products, this study used ethnobotanical and socioeconomic methods to engage communities in the Chimanimani Trans-Frontier Conservation Area, Mozambique. Use was dependent on local availability and market accessibility. Incomes are made from Uapaca kirkiana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Gathered in excess, they are sold in local markets to generate income, thereby contributing to the household economies of gatherers and collectors, usually women, or to bolster the incomes of migrants and unemployed moving from rural to urban areas [ 82 ]. For example, in the Chimanimani communities living in the Trans-Frontier Conservation Area in Mozambique, the fruits of Uapaca kirkiana and Strychnos madagascariensis are sold for a reasonable profit and represent an important source of income outside the maize harvest season (March to May) [ 83 ]. In their review paper, Hickey et al [ 84 ] showed that 50% of almost 8000 households sampled in forested areas of 24 developing countries across Asia, Africa, and Latin America derived their income from wild food collection.…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
See 1 more Smart Citation
“…Gathered in excess, they are sold in local markets to generate income, thereby contributing to the household economies of gatherers and collectors, usually women, or to bolster the incomes of migrants and unemployed moving from rural to urban areas [ 82 ]. For example, in the Chimanimani communities living in the Trans-Frontier Conservation Area in Mozambique, the fruits of Uapaca kirkiana and Strychnos madagascariensis are sold for a reasonable profit and represent an important source of income outside the maize harvest season (March to May) [ 83 ]. In their review paper, Hickey et al [ 84 ] showed that 50% of almost 8000 households sampled in forested areas of 24 developing countries across Asia, Africa, and Latin America derived their income from wild food collection.…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…Increased profits can often lead to overexploitation of WFPs and negative outcomes for the entire community [ 20 ]. To avert this possibility, participatory research is key to establish sustainable management guidelines and harvest rates, and to monitor the ecological impacts of increased use [ 83 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…More than 300 farmers in Mpunga and Mahate have been involved in apiculture and conservation farming (beans and sesame), and in Rotanda, many villagers have been undertaking horticultural and sesame farming; this NGO is also offering training, financial support, and market linkages to community members involved in these projects [interview, February 2018]. It was estimated that in 2017, 4,394 kg of honey was harvested, generating over US$3,000, while horticultural practices increased household income to US$84 (Hudson et al 2018). Related benefits were also apparently generated from ecotourism projects such as the MICAIA Tourism Project empowering youths and women to assume employment opportunities at Ndzou Camp in Moribane Forest [interview, February 2018].…”
Section: Access To Conservation Funding and Dispossession Through Con...mentioning
confidence: 99%
“…wild roots, medicinal plants, wild fruits, fuelwood etc.) which are all critical for household income and livelihoods (Hudson et al 2020) as well as shifting cultivation (particularly small grains, maize, legumes and sesame). As a primary habitat for multiple species, forests promote biodiversity conservation, stabilize stream ows and maintain water runoff.…”
Section: Study Site: the Chimanimani Borderland Regionmentioning
confidence: 99%